Model Pembelajaran Teams Games Tournaments (TGT) untuk Meningkatkan Hasil Belajar Siswa - Suwarno, Suwarno (Philanthropy: Journal of Psychology, 2019)
Abstract. This study aims to determine the effectiveness of the Teams Games Tournament (TGT) learning model to improve student learning outcomes. This research is important because the lecture learning model makes learning meaningless so it impacts on low learning outcomes. This research uses quasi experiment using control class and experimental class. Respondents in this study were students of class X SMK 8 Semarang Academic Year 2017/2018. Sample selection using random sampling, class X1 is used as a control class and X2 is an experimental class. The experimental class was given an intervention by learning Teams Games Tournaments (TGT), while the control class used lecture learning. The effectiveness of the model was measured by the student test analysis method. then analyzed by completeness test and average difference test. The findings of this study are the learning outcomes of experimental class students achieving better learning outcomes than classes using the lecture method.Keywords: Learning Model, Teams Games Tournaments (TGT). StudentsDaftar Pustaka  Bofota, Y. B., & Bofota, Y. B. (2017). The impact of social capital on children educational outcomes €¯: the case of Tanzania The impact of social capital on children educational outcomes €¯: The case of Tanzania.Cahuc, P., Shleifer, A., & Algan, Y. (2014). Teaching Practices and Social Capital. (6052).Catts, R., & Ozga, J. (2015). What is Social Capital and how might it be used in Scotland s Schools €¯? (36).Flint, N. (2017). Full report Schools , communities and social capital €¯: building blocks in the Big Society Contents.Goddard, R. D. (2016). Relational Networks , Social Trust , and Norms €¯: A Social Capital Perspective on Students Chances of Academic Success. 25(1), 59 74.Eddy Prasongko, 2017. Team Game Tournament. Bandung. Jawa BaratEndang Poerwanti, dkk. 2008. Asesmen Pembelajaran SD. Jakarta: Direktorat Jendral Pendidikan Tinggi Departemen Pendidikan NasionalHargreaves, A. (2015). School Social Capital and School Effectiveness. 37, 119 136.Kurnia, Inggridwati. dkk. 2018. Perkembangan belajar peserta didik. Jakarta: Direktorat Jendral Pendidikan Tinggi Departemen Pendidikan NasionalPurwanto. M Ngalim. 2015. Psikologi Pendidikan. Bandung: PT Remaja RosdakaryaSiddiq, M. Djauhar. 2018. Pengembangan Bahan Pembelajaran SD. Jakarta: Direktorat Jendral Pendidikan Tinggi Departemen Pendidikan Nasional.Sugiyono, 2005. Metode Penelitian Kuantitatif, Kualitatif dan Rn D, Bandung AftabetaLash, D., & Belfiore, G. (2017). 5 Essentials in Building Social Capital Report 4 of the MyWays Student Success Series. (October).Mikiewicz, P., Jonasson, J. T., Gudmundsson, G., Blondal, K. S., & Korczewska, D. M. (2011). Comparative research between Poland and Iceland.Schlesselman, L., Borrego, M., Bloom, T. J., Mehta, B., Drobitch, R. K., & Smith, T. (2015). An Assessment Of Service-Learning In 34 US Schools Of Pharmacy Follow Up On The 2001 Professional Affairs Committee Report. American Journal of Pharmaceutical Education, 79(8). https://doi.org/10.5688/ajpe798116